2019
DOI: 10.56093/ijans.v89i2.87342
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of udder morphometry with milk yield and body condition traits in Beetal goats

Abstract: Present study was conducted to find the relationship of udder morphometry with milk yield and body condition traits in Beetal goats. Beetal goats (60) having 4 different parities were used. Udder (length, column width, row width, depth, circumference, volume) and teat (length, diameter, circumference, height from ground, inter teat distance) morphological traits were recorded just before morning milking at fortnightly interval up to 3 months post-kidding stage. Simultaneously, milk yield (morning and daily) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…This developmental process is mainly regulated by hormones, growth factors, and cytokines. Jena et al [37] recorded the morphological characteristics of the udder (length, column width, row width, depth, circumference, volume) and teat (length, diameter, circumference, height from the ground, inter-teat distance) of goats alongside daily milk yield over three months. Correlation analysis showed that all the teat traits were positively correlated with daily milk yield.…”
Section: Udder Traitsmentioning
confidence: 99%
“…This developmental process is mainly regulated by hormones, growth factors, and cytokines. Jena et al [37] recorded the morphological characteristics of the udder (length, column width, row width, depth, circumference, volume) and teat (length, diameter, circumference, height from the ground, inter-teat distance) of goats alongside daily milk yield over three months. Correlation analysis showed that all the teat traits were positively correlated with daily milk yield.…”
Section: Udder Traitsmentioning
confidence: 99%
“…The phenotypic relationship between zoometrics and dairy production (either milk yield, components, or even transformed products, such as cheese) has been investigated (17)(18)(19) and tools seeking the optimal dairy goat type have been developed (13,15,16,20,21). As a result, some methods have been developed for predicting daily milk production and the performance of milk components from morphometry and linear appraisal (22,23).…”
Section: Introductionmentioning
confidence: 99%